2015
DOI: 10.1016/j.cattod.2014.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids breakdown by Fenton oxidation

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: Upon Fenton oxidation of the four ILs tested hydroxylated compounds of higher molecular weight than the starting ILs, fragments of ILs partially oxidized and short-chain organic acids were identified as reaction by-products. Reaction pathways are proposed.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 33 publications
9
41
0
Order By: Relevance
“…Although the viability of the process has been demonstrated, since the complete conversion of the IL Fenton oxidation under the operating conditions previously reported [21,22] and the ecotoxicity of the non-treated and treated effluent. The evolution of the chemical oxygen demand (COD), Total Organic Carbon (TOC), the type of acids formed and the toxicity of the Fenton oxidation effluents towards the Vibrio fischeri marine luminescent bacteria, upon oxidation were evaluated.…”
Section: Introductionmentioning
confidence: 97%
“…Although the viability of the process has been demonstrated, since the complete conversion of the IL Fenton oxidation under the operating conditions previously reported [21,22] and the ecotoxicity of the non-treated and treated effluent. The evolution of the chemical oxygen demand (COD), Total Organic Carbon (TOC), the type of acids formed and the toxicity of the Fenton oxidation effluents towards the Vibrio fischeri marine luminescent bacteria, upon oxidation were evaluated.…”
Section: Introductionmentioning
confidence: 97%
“…The chemical nature of the degradation products is also relevant in order to evaluate if these compounds are environmentally friendlier than their precursors. Siedlecka et al [16] and more recently Muñoz et al [17] showed that the main degradation products of methylimidazolium cations in aqueous solutions under Fenton oxidation are imidazolones. On the other hand, Czerwicka et al [18] showed that the photochemical treatment of methylimidazolium cations in solution with UV/H 2 O 2 yields main degradation products with two hydroxyl groups at the imidazolium ring.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Fenton oxidation is receiving growing attention and has been successfully applied . In recent contributions, we reported complete disappearance of imidazolium‐based ILs ([IL] 0 = 1000 mg L −1 ) and more than 50% mineralization under optimum operating conditions ([Fe 3+ ] = 50 mg L −1 ; stoichiometric dose of H 2 O 2 ; 70–90 °C). Non‐toxic effluents were obtained after 4 h treatment.…”
Section: Introductionmentioning
confidence: 99%